Pemberian Edukasi Kepada Masyarakat Pemanfaatan Kulit Buah Pir Menjadi Sediaan Sheet Mask yang berkhasiat sebagai Antioksidan - Monica Suryani; Manahan Situmorang; Steven Tandiono; Cut Masyitah Thaib (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Pear skin contains flavonoids which have potential as antioxidants. Considering the existence of humans as social creatures, who in interacting with each other require self-confidence in order to be well received. Masks are a type of cosmetic treatment that is well known and widely used. The mask works deeply to remove dead horn cells on the skin. The aim of this community service is to provide education to the public about the benefits of pear skin as an antioxidant. This method of community service is by providing education to the public by presenting material about pear peels which are used as antioxidants and introducing natural ways to use pear peels. The results of the activities of implementing the community service program are in the form of educating the public about the benefits of pear skin, namely as an antioxidant. Conclusion: Community service in managing pear skin as an antioxidant meets quantity and quality.